BENTUK PENYAJIAN RONGGENG DALAM UPACARA ADAT TURUN MANDI ANAK DI MUARO KIAWAI KECAMATAN GUNUANG TULEH KABUPATEN PASAMAN BARAT - Nuzula Mustika; Jagar Lumban Toruan; Syeilendra Syeilendra (SENDRATASIK UNP, 2014)
Abstract This research was aimed at describing the presentation of Ronggeng in Maantaan Kambiang of Traditional Ceremony of Turun Mandi in Muaro Kiawai Kecamatan Gunuang Tuleh Kabupaten Pasaman Barat. Ronggeng wich was presented in the ceremony had supporting element which were the players, musical instruments, song, customs, time and place of the show, and audiences. In the procession of Maantaan Kambiang, Ronggeng presented was in the form of musical show that consisted of some musical instruments to accompany the Ronggeng songs. These were performed along the way from the male house to the female house. Keywords: Presentation, Ronggeng